An investigation of emerging music courses in Colorado secondary schools - Cort, Madeleine, author (Colorado State University. Libraries, 2021)
Emerging Music Courses (EMCs) are music classes for secondary students outside of traditional ensemble offerings and include courses in composition, music theory, music technology, guitar, piano, and general music. These classes are a growing trend and are an access point to music learning for students who play an instrument not offered in ensembles, are not enrolled in traditional ensemble courses, or have musical interests outside of ensemble performance. The purpose of this study is to determine the prevalence of EMCs in Colorado's secondary schools, examine the learning activities used in EMCs, explore the beliefs teachers have about music learning in EMCs, and the impact of the COVID-19 pandemic on these courses. Data for this study will be collected using a descriptive survey method and post-questionnaire interviews. The questionnaire will be administered to music teachers employed by a public secondary school in the state of Colorado during the 2021-2022 school year. Follow-up interviews will utilize a maximum variation sampling strategy to identify participants that teach EMCs in a variety of contexts and who represent a range of individual demographic differences. Data collection and analysis will be completed in January 2022. Expected results include a growth in the prevalence of EMCs in Colorado and evidence of a wide variety of learning activities that differ significantly from traditional ensemble courses. Teacher beliefs are likely mixed and will depend on independent situations and backgrounds. This study will help teachers and schools make informed decisions about their course offerings and illuminate best practices in EMCs.
The following poster and videos were originally submitted as part of the CSU Graduate Student Showcase in the Fall of 2021. The materials are a summary of the author's in-progress Mater's thesis project titled, "An Investigation of Emerging Music Courses in Colorado Secondary Schools."
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: music; music education; education; guitar; piano; music technology